GEOMETRIC CORRECTION OF AERIAL PHOTOGRAPH OF SCANNING 600 DPI ` MEASUREMENT OF A COASTAL AREA (TAMBAKHARJO) - Sardiyatmo . (JOURNAL OF COASTAL DEVELOPMENT, 2000)
The objective of this research was to investigate how far is the deviation in measurement of an area of aerial photograph scanning 600 dpi 1 .· 5500 scale compared with the photographic map of I .· 1000 scale in Semarang municipality along with the use for measurement of the extent of land area. In order to scan 600 dpi the product of the geometry correction can be used to calculate the extent ofthe land area at an accuracy level of 0.38 m.